Efektivitas Penggunaan Kitab Nazham ‘Ilmu Tajwid pada Kelas VII di MTs Al-Burhan Bandung - Aprilyani, Indah; Ikin Asikin; Alhamuddin (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2025)
The reading ability of the Qur'an among the Indonesian community still does not align with the rules of tajwid. This research aims to measure the effectiveness of using the Kitab Nazham Ilmu Tajwid in understanding tajwid and its impact on the reading skills of Qur'an among seventh-grade students at MTs Al-Burhan Bandung. The study employs a quantitative approach with a quasi-experimental method. Both the control and experimental groups were given pre-tests and post-tests, but only the experimental group received treatment through the use of the Kitab Nazham 'Ilmu Tajwid. This allows the measurement of the treatment's effect on the understanding of tajwid and the ability to read the Qur'an. The study shows that the implementation of the Kitab Nazham 'Ilmu Tajwid at MTs Al-Burhan Bandung occurred through three stages: reciting the nazham (using bandongan and sorogan methods), breaking down the meanings, and practicing the identification and recitation of tajwid rules. This book also serves as a medium for strengthening culture and literature in learning. The results indicate that its use is effective in improving the understanding of tajwid and the ability to read the Qur'an, evidenced by the post-test results and significant statistical tests. A positive correlation between the understanding of tajwid and the ability to read the Qur'an further supports these findings. The supporting factors for learning include an integrated Qur'an learning program, teacher competence, and a religious school environment. However, challenges include students' language limitations, limited study time, less varied methods, and a lack of supporting digital media.